Urgensi Pembentukan Aturan Induk bagi QRIS untuk Menjamin Perlindungan Hukum Bagi Konsumen dalam Integrasi Transaksi ASEAN - Muthia Zahra Qurraatha Aini (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2026)
The digitalization of payment systems constitutes an integral part of economic digital transformation, driving a shift in transactions from cash-based to technology-based cashless payments. In Indonesia, this digitalization is manifested through the development of the Quick Response Code Indonesian Standard (QRIS) by Bank Indonesia as a national standard for QR code–based payments. Along with its development, QRIS has not only been used in domestic transactions but has also been implemented in cross-border transactions through intercountry payment system cooperation, particularly within the ASEAN region. However, the rapid expansion of QRIS has not been accompanied by comprehensive and structured legal regulation. This study aims to analyze the structure and hierarchy of QRIS regulation within Indonesia’s payment system as well as the forms of legal protection for consumers in cross-border QRIS transactions. The research employs a normative juridical method using statutory, historical, and conceptual approaches. The findings indicate that QRIS does not yet have a Bank Indonesia Regulation as a primary regulatory framework and is regulated solely through a Regulation of Members of the Board of Governors, which hierarchically functions as an implementing regulation. Consequently, QRIS regulation refers to several different Bank Indonesia Regulations, resulting in regulatory fragmentation. This condition has implications for legal uncertainty and the suboptimal legal protection of consumers in cross-border QRIS transactions.